Analisa Daya Rekat Cat dengan Variabel Surface Roughness, Temperatur Substrat dan Jenis Material Abrasif Menggunakan Metode Taguchi - Arum Sukma Mutiara; Farizi Rachman; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
PT Lintech Duta Pratama is one of the manufacturing companies where in the process there is a finishing and painting manufacturing process. Painting is done with the aim of inhibiting the rate of corrosion and improving product appearance. Improper painting process results in defects. Products that have defects require repair so that they can then be sent to customers. Repeated repair processes cause delays in product delivery. To get products with good quality, research is needed to get the optimal combination of process parameters in the painting process. The process parameters studied are surface roughness, substrate temperature, and abrasive material type. The experimental design uses the taguchi method in the form of an orthogonal matrix L_9(3^4) with three replications. From the experimental results, the optimal combination of process parameters on adhesion and process cost simultaneously on paint adhesion was obtained, namely surface roughness at level 1 with a value of 50, substrate temperature at level 2 with a value of 34°C, and abrasive material type at level 1 with garnet abrasive. The surface roughness parameter gives a percentage contribution of 14.56%, substrate temperature 0.48%, and abrasive material type 84.28%.